Empathy's Role in Understanding Persons, Literature, and Art - Petraschka, Thomas; Werner, Christiana (Routledge Studies in Contemporary Philosophy, 2024)
This volume critically discusses the role empathy plays in different processes of understanding. More precisely, it clarifies empathy's role in interpersonal understanding and appreciating works of literature and art. The volume also includes a section on historical theories of empathy's role in understanding. When it comes to understanding other persons, empathy is typically seen as a process that enables the empathizer to recognize a target person's mental states, a process which is in turn seen as "understanding" this person. This volume, however, explores empathy's role in understanding beyond mere mental state recognition. With contributions on processes of interpersonal understanding and understanding of literature and art, it provides readers with an overview over both differences and similarities regarding empathy's epistemic role in two rather different areas. Since important roots of the debate about empathic understanding lie at the end of the nineteenth and the beginning of the twentieth century, the historical section of the volume focusses specifically on this period. Empathy's Role in Understanding Persons, Literature, and Art will appeal to scholars and advanced students working in the philosophy of mind, epistemology, aesthetics and the history of philosophy, as well as in literary studies and art history.